2018
DOI: 10.20546/ijcmas.2018.704.375
|View full text |Cite
|
Sign up to set email alerts
|

Pesticides Usage and Handling by the Tomato Growers in Ramanagara District of Karnataka, India – An Analysis

Abstract: A study was conducted to analyze the perception and pesticides usage practices by the small tomato growers in Ramanagara district of Karnataka using the pretested questionnaire and field observations. Detailed Information was obtained from 129 tomato growers wherein the information related to extent and types of pesticides used, knowledge about pesticides and their effectiveness was collected. Most of the respondents (98.44%) were male and most commonly farmers use 25 pesticides in tomato ecosystem. The major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…6 indicates that majority of the respondents (52 percent) applied the pesticides using the knapsack sprayer and remaining respondents (48 percent) used power operated sprayer. The results of the study was found to be similar as reported by keshavareddy et al (2018) [5] .…”
Section: Methods Of Pesticide Applicationsupporting
confidence: 90%
See 1 more Smart Citation
“…6 indicates that majority of the respondents (52 percent) applied the pesticides using the knapsack sprayer and remaining respondents (48 percent) used power operated sprayer. The results of the study was found to be similar as reported by keshavareddy et al (2018) [5] .…”
Section: Methods Of Pesticide Applicationsupporting
confidence: 90%
“…The tomato growing farmers in Anantapur district used various agrochemicals to control the pest incidence. Kesavareddy et al (2018) [5] . analyzed the perception and pesticides usage practices by the small tomato growers in Ramanagara district of Karnataka and reported that farmers use more than 25 pesticides in tomato ecosystem.It was surprising to note that farmers had no preference for a particular product and dealers/retailers could easily influence the pattern of buying pesticides.…”
Section: Introductionmentioning
confidence: 99%
“…These facts indicate similarities in the circulation and use of various AI in Mexico and South America. In addition, there is evident abuse in the application of various pesticides individually and in mixtures, as occurs in other similar production systems in India (13) and Ghana (6). Concerning mixtures, underreporting of pesticide application is likely due to fear of sharing which mixtures they consider more successful in preventing or controlling pests and diseases.…”
Section: Discussionmentioning
confidence: 99%
“…It is a low calorie vegetable, low in fat, has no cholesterol and is an excellent source of anti-oxidants, dietary fiber, minerals, potassium and vitamins. Eating tomatoes has been promoted as helping to prevent some human diseases (cancer and heart diseases) and improving the immune system response [3][4][5]. Using insecticides and fungicides is inevitable for the management of insect pest and disease incidence but it causes resurgence, resistance and residue problems in the agroecosystems.…”
Section: Short Research Articlementioning
confidence: 99%